Evaluation of Bored Pile Axial Capacity Using Empirical Methods and Field Tests - Alexander Genkensiana; Andrias Suhendra Nugraha; Darlene Priscilla Kaway (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2026)
Bored piles are widely used as deep foundation systems to support heavily loaded structures, particularly in areas with soft surface soils. Accurate estimation of axial bearing capacity is essential to ensure foundation safety and structural performance. This study evaluates the axial bearing capacity of bored pile foundations using the empirical methods proposed by Reese and O'Neill (1989) and Meyerhof (1976), with verification through field testing. The analysis was conducted on bored piles with a diameter of 1000 mm and a working load of 450 tons in a multistory building project located in North Jakarta, Indonesia. Ultimate bearing capacities obtained from the empirical methods were compared with results from Static Loading Tests interpreted using the Mazurkiewicz method and Pile Driving Analyzer (PDA) Tests. Reese and O'Neill predicted ultimate capacities ranging from 1108 to 1116 tons, while Meyerhof produced values between 1132 and 1139 tons. Field verification yielded ultimate capacities of 845–905 tons from the Static Loading Tests and 1285–1350 tons from the PDA Tests. The Reese and O'Neill method provided estimates closer to the field-based static loading results than the Meyerhof method. These findings demonstrate the importance of field verification in evaluating empirical design methods and provide practical guidance for selecting appropriate approaches for bored pile foundation design under similar soil conditions.